2010
DOI: 10.3402/rlt.v18i1.10673
|View full text |Cite
|
Sign up to set email alerts
|

Medical students' perceptions of video-linked lectures and video-streaming

Abstract: Video-linked lectures allow healthcare students across multiple sites, and between university and hospital bases, to come together for the purposes of shared teaching. Recording and streaming video-linked lectures allows students to view them at a later date and provides an additional resource to support student learning. As part of a UK Higher Education Academy-funded Pathfinder project, this study explored medical students' perceptions of video-linked lectures and video-streaming, and their impact on learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 9 publications
2
13
0
Order By: Relevance
“…Students perceived the greatest strength of the online format to be their ability to control the instructional pace of archived lectures, and to a smaller extent, laboratories. This finding is reflected in literature on medical students’ perceptions of learning from pre‐recorded lectures (Cardall et al, ; Wang et al, ; Beale et al, ). However, studies of medical students in their first and second year also found that the primary decision to watch a lecture online versus F2F was driven by reasons related to the specific instructor (Billings‐Gagliardi and Mazor, ; Wang et al, ; Gupta and Saks, ).…”
Section: Discussionmentioning
confidence: 59%
“…Students perceived the greatest strength of the online format to be their ability to control the instructional pace of archived lectures, and to a smaller extent, laboratories. This finding is reflected in literature on medical students’ perceptions of learning from pre‐recorded lectures (Cardall et al, ; Wang et al, ; Beale et al, ). However, studies of medical students in their first and second year also found that the primary decision to watch a lecture online versus F2F was driven by reasons related to the specific instructor (Billings‐Gagliardi and Mazor, ; Wang et al, ; Gupta and Saks, ).…”
Section: Discussionmentioning
confidence: 59%
“…One of the most popular reasons noted in the literature for students favoring recorded lessons is the ability to control the instructional pace, and similar findings were reported in the previous year of the course (Attardi et al, ). The student's strong desire to control the delivery of information is not unique to the undergraduate level and has also been reported in studies on medical students' perceptions of learning from recorded lessons (Cardall et al, ; Wang et al, ; Beale et al, ; Singh and Min, ). Students may have perceived the benefit of pace control to be greater than the opportunity to interact live with their professors and TAs.…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, the findings of our study are consistent with previous research in dental education and other disciplines that found support for the use of videos as an adjunct to classroom teaching. 11,[17][18][19]21,[24][25][26][27][28][29][30] Our findings suggest dental hygiene instrumentation videos can be successful in improving learning by meeting the needs of students to supplement traditional teaching of clinical skills.…”
Section: Discussionmentioning
confidence: 99%
“…10 While instrumentation videos are a relatively new adjunct to teaching dental hygiene instrumentation skills to students, the use of video as an instructional aid has been widely studied in health professions education. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Holland et al found that online video was an effective instructional method for nursing students in developing clinical skills. 11 Other studies reported that using video as a pedagogic tool increased engagement of nursing students and provided useful conceptual links between theory and practice.…”
mentioning
confidence: 99%